The Correlation Between Parental Stimulation and Motor Development in Stunted Toddlers - Santoso, Yuanita Devi; Efendi, Ferry; Kurnia, Iqlima Dwi; Susanti, Ika Adelia; Pramono, Ahmad Putro; Habibie, Aziz Nashiruddin (International Journal of Psychosocial Rehabilitation, 2020)
Stunted toddlers cannot explore their fine and gross motor skills because they tend to have shorter body and change in brain structure and function in brain development caused by the late maturity of cerebellum cells. Stimulation plays an essential role in improving child development, especially children’s motor development. This study aimed to analyze the role of parents’ stimulation in motor development in stunted toddlers. The study design used was a cross-sectional approach. The sample was 96 mothers, with their stunted toddlers using simple random sampling. Parental stimulations was the independent variable and motor development was the dependent variable. Data collection used the Denver Developmental Screening Test (DDST) questionnaire. Data were analyzed using the Spearman rank correlation test with a significance p